KUALITAS SPERMATOZOA DARI TANAMAN Polyscias guilfoylei - Elya, Berna; Kusmana, Dadang; Krinalawaty, Nevy (Makara Journal of Science, 2010)
Spermatozoa Quality from Polyscias guilfoylei. In our study, we investigated the effect of extract Polyscias guilfoylei L.H. Bailey leaves on spermatozoa quality in rabbits. The experiment used 18 male rabbits from New Zealand white strain which were devided randomly into three groups. Group I was normal control group, Group II and III were given the extract of Polyscias guilfoylei leaves in these following doses: 327.56 mg/1.5 kg body weight and 655.2 mg/1.5 kg bw. The extract was given orally once a day, continuously for 8 weeks. Semens from the rabbit was taken every two weeks and were observed over the quality and consentration of spermatozoa. The result of the research showed that the extract of Polyscias guilfoylei leaves with dosage of 327.56 mg/1.5 kg bw and 655.2 mg/1.5 kg bw could decrease the consentration and the quality of spermatozoa of the male rabbits